Cancer Risk Analysis Based on Improved Probabilistic Neural Network - Yang, Chaoyu; Yang, Jie; Liu, Ying; Geng, Xianya (Frontiers in Computational Neuroscience, 2020)
The problem of cancer risk analysis is of great importance to health-service providers and medical researchers. In this study, we propose a novel Artificial Neural Network (ANN) algorithm based on the probabilistic framework, which aims to investigate patients' pattern associated with their disease development. Compared to the traditional ANN where input features are directly extracted from raw data, the proposed probabilistic ANN manipulates original inputs according to their probability distribution. More precisely, the models of Naive Bayes and Markov chain are used to approximate the posterior distribution of the raw inputs, which provides a useful estimation of subsequent disease development. Later those distribution information is further leveraged as additional input to train ANN. Additionally, to reduce the training cost and boost the generalization capability, a sparse training strategy is also introduced. Experimentally, one of the largest cancer-related datasets is employed in this study. Compared to state-of-the-art methods, the proposed algorithm achieves a much better outcome, in terms of the prediction accuracy of subsequent disease development. The result also implies the potential impact of patients' disease sequence on their future risk management.